PIF4 Promotes Expression of LNG1 and LNG2 to Induce Thermomorphogenic Growth in Arabidopsis - Hwang, Geonhee; Zhu, Jia-Ying; Lee, Young K.; Kim, Sara; Nguyen, Thom T.; Kim, Jungmook; Oh, Eunkyoo (Frontiers in Plant Science, 2017)
Arabidopsis plants adapt to high ambient temperature by a suite of morphological changes including elongation of hypocotyls and petioles and leaf hyponastic growth. These morphological changes are collectively called thermomorphogenesis and are believed to increase leaf cooling capacity by enhancing transpiration efficiency, thereby increasing tolerance to heat stress. The bHLH transcription factor PHYTOCHROME INTERACTING FACTOR4 (PIF4) has been identified as a major regulator of thermomorphogenic growth. Here, we show that PIF4 promotes the expression of two homologous genes LONGIFOLIA1 (LNG1) and LONGIFOLIA2 (LNG2) that have been reported to regulate leaf morphology. ChIP-Seq analyses and ChIP assays showed that PIF4 directly binds to the promoters of both LNG1 and LNG2. The expression of LNG1 and LNG2 is induced by high temperature in wild type plants. However, the high temperature activation of LNG1 and LNG2 is abolished in the pif4 mutant, indicating that PIF4 directly regulates LNG1 and LNG2 expression in response to high ambient temperatures. We further show that the activities of LNGs are required for thermomorphogenic growth. The expression of auxin biosynthetic and responsive genes is decreased in the lng quadruple mutant, implying that LNGs promote thermomorphogenic growth by activating the auxin pathway. Together, our results demonstrate that LNG1 and LNG2 are directly regulated by PIF4 and are new components for the regulation of thermomorphogenesis.